Implementation of Use of Warm Compress Therapy to Lower Body Temperature in Patient with Dengue Hemorrhagic Fever - Gunawan, Asep; Nur'apipah, Pipih; Dwi Mulyani, Mutia; Suhanda; Hidayat, Nur (Yayasan Inspirasi El Burhani, 2022)
Objective : To provide direct nursing care to children who have hyperthermia problems in the Melati Room, Banjar City Hospital. Method: The research design used is descriptive analysis with a case study approach using nursing care that refers to the IDHS and SIKI books. The subjects of this case study were children with DHF with hyperthermia problems in the Melati Room of the Banjar City Hospital, in the use of data collection techniques ranging from interviews, observation, physical examinations and documentation studies. Result : This can be seen in the results of the case study stage, it is known that the patient complains of fever. Interventions and implementations carried out to reduce fever were by giving warm compresses in the forehead area for 10-15 minutes, body temperature before warm compresses was 37.80c, and after being given a warm compress intervention the temperature was 37.50c. Conclusion : The conclusion of nursing care on the effect of warm compresses can affect the decrease in temperature in DHF patients with hyperthermia problems. Warm compress intervention effectively lowers body temperature.